2018
DOI: 10.2147/ott.s170482
|View full text |Cite|
|
Sign up to set email alerts
|

SNHG8 is identified as a key regulator in non-small-cell lung cancer progression sponging to miR-542-3p by targeting CCND1/CDK6

Abstract: BackgroundRecently, various dynamically expressed lncRNAs are known to play critical roles in cancer progression. Small nucleolar RNA host genes (SNHG), a stable cytoplasmic lncRNA, which have been widely reported to act as an oncogene in non-small cell lung cancer (NSCLC). As an important member of SNHG, SNHG8 have been suggested to over-expressed in several cancer disease, while the biological function in NSCLC remains unclear.PurposeHere we investigated the biological function and underlying mechanism of SN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 23 publications
2
33
0
Order By: Relevance
“…Recently, many studies have found that the aberrant expression of snoRNAs might act as an oncogene in the progression of the tumor. For example, Chen found that SNHG8 overexpressed in non-small cell lung carcinoma (NSCLC) [32], and Dong found that SNHG8 is an oncogene in human hepatocellular carcinoma [33], Meng found SNHG6 promotes glioma tumorigenesis in glioma [34], and Zhu found SNHG4 overexpressed in hepatocellular carcinoma [35]. Consistent with these studies, we found higher SNHG4 expression in liver cancer and it may be a biomarker.…”
Section: Discussionsupporting
confidence: 86%
“…Recently, many studies have found that the aberrant expression of snoRNAs might act as an oncogene in the progression of the tumor. For example, Chen found that SNHG8 overexpressed in non-small cell lung carcinoma (NSCLC) [32], and Dong found that SNHG8 is an oncogene in human hepatocellular carcinoma [33], Meng found SNHG6 promotes glioma tumorigenesis in glioma [34], and Zhu found SNHG4 overexpressed in hepatocellular carcinoma [35]. Consistent with these studies, we found higher SNHG4 expression in liver cancer and it may be a biomarker.…”
Section: Discussionsupporting
confidence: 86%
“…25 Furthermore, SNHG8 is overexpressed in non-small cell lung cancer tissues and cell lines. 26 Patients with non-small cell lung cancer overexpressing SNHG8 show shorter overall survival and shorter progression-free survival relative to the patients with low SNHG8 expression. 26 However, the expression profile and clinical value of SNHG8 in ESCC have remained elusive and merit research.…”
Section: Discussionmentioning
confidence: 98%
“…26 Patients with non-small cell lung cancer overexpressing SNHG8 show shorter overall survival and shorter progression-free survival relative to the patients with low SNHG8 expression. 26 However, the expression profile and clinical value of SNHG8 in ESCC have remained elusive and merit research. In this study, we found that SNHG8 expression is high in ESCC tissues and cell lines.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Herein, SNHG8, was agreed as a potent multiple tumor facilitator in previous research. [15][16][17][18][19] One thing we have in common with previous studies was that SNHG8 was upregulated and aggravated tumorigenesis. However, the stimulating effect of SNHG8 in HPV-positive CC cells was first disclosed in the present study.…”
Section: Discussionmentioning
confidence: 99%